Penguatan Usaha Ekonomi Pesantren Berbasis Kawasan Pada Pondok Pesantren Salafiyah Syafi’iyah Kecamatan Randangan Kabupaten Pohuwato Gorontalo - Syawaluddin Syawaluddin (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
Pesantren-based education today is no longer dominated by religious knowledge but has undergone a scientific transformation by combining general and religious knowledge. One of the important educational elements in Islamic boarding schools is to equip students with life skills (life skiing) to support the religious education they receive, this is so that one day the students will have the ability to identify problems and how to overcome these problems. This study aims to provide an area-based strengthening of the pesantren economy using the PAR approach, by directly involving pesantren residents, especially the students, to identify and solve economic potential problems that can be developed. The result is that Islamic boarding schools can develop several food products for the people whose raw materials are based on local potential, such as corn chips, fried rambutan, jengkol crackers and others, in addition to cattle fattening programs, paint production and urine fertilizer, it is still possible to develop them.